The Implementation of the Management Processes of Mobile Hospital Health Services in the Province of Maguindanao - Macasayon, Mocamad (JPAIR Multidisciplinary Research, 2018)
Although agreement about the need for quality improvement in healthcare is almost universal, the means of achieving effective improvement in overall care is not well understood. Mobile hospital health interventions could have beneficial effects on healthcare delivery processes. This study explored the extent of the implementation of the management processes of Mobile Hospital health services. The study used the descriptive correlation method of research. Survey questionnaires were used to collect data from health workers from different municipalities of the province of Maguindanao. The study shows that the management processes of the mobile health services in terms of planning, organizing, staffing, implementation, monitoring, and evaluation were properly implemented. The study implies that the Mobile Hospital health services in the Province of Maguindanao through the application of management processes are effective.